PERBEDAAN KADAR MALONDIALDEHYDE (MDA) PASIEN COMMUNITY ACQUIRED PNEUMONIA (CAP) PADA PEROKOK DAN BUKAN PEROKOK DI RSUD GERUNG - Linda Irma Septiana; Sahrun; Shinta Wulandhari; IGP Winangun (Nusantara Hasana Journal, 2023)
Pneumonia is an inflammation that occurs in the lung parenchyma, distal to the terminal bronchioles which include the respiratory bronchioles and is accompanied by consolidation in the lung tissue. In 2021, pneumonia will become the first most lung health problem in West Lombok. The risk factor for CAP is smoking. This study aims to differentiate MDA levels of CAP patients in smokers and non-smokers at Patut Patju Gerung General Hospital, West Lombok. This study used a retrospective method with a case control study design using medical record measuring instruments. A total of 42 research samples were carried out using a purposive sampling technique in community pneumonia patients (CAP) at Patut Patuh Patju Gerung Hospital, West Lombok from data from May to July 2022. Bivariate analysis was tested using the mann-whitney. The results of the analysis of the data obtained from the 42 samples found that the most respondents were those with malondialdehyde (MDA) levels which increased by 25 people with a percentage (59.5%). Based on the analysis of the data obtained from the 21 sample cases, it was found that the majority of respondents were those with malondialdehyde (MDA) levels which increased by 15 people with a percentage (71.42%). While the control sample found that respondents with low MDA values had the same number of respondents who had increased MDA values by a total of 10 people with a percentage (47.6%). It was found that the P-Value was 0.564 > 0.05, so it can be concluded that there was no difference in MDA levels between smokers and non-smokers in the case group and the control group. Statistically, there was no difference in MDA levels between smokers and non-smokers in both the case group and the control group, but at the Patut Patuh Patju Gerung Regional General Hospital, West Lombok.